The effectiveness of RHB Bank promotion mix / Nurul Hidayah Hasbullah - Hasbullah, Nurul Hidayah (2011)
Nowadays, in the real business world companies start realizes the significant importance of marketing promotion mix especially banking sector in order to deliver the message to their customers effectively. Marketing promotion mix can influence company’s performance especially for retail based company since it involved customers perception. However not all companies practice the same marketing promotion mix which some of them have may use difference tools to communicate with their customers. Marketing promotion mix is really important to banking sector as we can see now, banks grow like mushrooms and to stay competitive and be selected by customers they need to use marketing promotion mix as a medium to communicate with their customers regarding products and services that they offer to customers. This is because people nowadays realize the importance of bank as a safe place to keep their cash or valuable assts. Most of the banks offer same products and services which the main service is to secure their customers cash or valuable asset and at the same time they can make a profit. Thus, customers tend to be very selective since it involves their valuable assets and money and only loyal customers will remain and use the same bank. Thus, to retain this kind of customers as well as to attract new customers, they offer new promotion or re-launch the existing promotion to the customers.